Strategi Pemasaran Media Sosial dalam Membangun Kesadaran Merek Produk Qardhul Hasan - Anang Hidayah; Siti Rokhaniyah (CV. ITTC INDONESIA, 2026)
This study aims to examine the digital communication strategy of BMT Barokah Tegalrejo in building public awareness of the Qardhul Hasan product. A qualitative descriptive-explorative approach was employed, with data collected through interviews, observation, and digital documentation during an internship period from January 5 to March 13, 2026. The findings reveal that the implemented strategy encompasses four main dimensions: educational content, human interest, active engagement, and brand consistency across Instagram and Facebook platforms. This study also identifies potential barriers along with mitigation measures, ranging from algorithm dynamics, limited human resources, low public literacy on Islamic financial products, to slow digital interaction responses. This study concludes that the synergy between the social mission of Qardhul Hasan and an effective digital communication strategy is capable of strengthening brand awareness and promoting sustainable Islamic financial inclusion.